Depolarization-independent net uptake of calcium into clonal insulin-releasing cells exposed to glucose. Issue 10 (October 1983) - Gylfe, Erik; Andersson, Tommy; Rorsman, Patrik; Abrahamsson, Håkan; Arkhammar, Per; Hellman, Per; Hellman, Bo; Oie, Herbert K.; Gazdar, Adi F.
Abstract : Insulin release, net fluxes of Ca 2+, and glucose metabolism were studied in a clonal cell line (RINmSF) established from a transplantable rat islet tumor. The insulin content amounted to only 0.03% of that of the total protein and decreased even further with subsequent passages. The insulin secretion was as high as 10 to 20% of the total hormone content per hour. Insulin release was stimulated by K + depolarization but not by exposure to glucose. In contrast to this secretory pattern, glucose but not K + stimulated the net uptake of Ca 2+ at micromolar concentrations of the ion. The glucose effect was not mimicked by 20 mM 3-O-methylglucose. It was as pronounced at 1 mM as at 20 mM of the sugar and corresponded to an uptake of 119 fmol cm −2 s −1 . Glucose metabolism was typical for tumor cells with a high glycolytic flux and an oxidationtoutilization ratio as low as 0.05–0.15. Maximal oxidative degradation was attained already at l mM. This concentration was also equivalent to the Km for glucose utilization, indicating a substantial left-hand shift of the normal dose-response curve. It is suggested that glucose induces a depolarizationindependent net uptake of Ca 2+ by favouring intracellular buffering of the cation.